YESUS SEBAGAI GURU DAN KONSELOR: MEMAHAMI DUA FUNGSI UTAMA DALAM MISI-NYA - Agrendi Mangali; Harjen Kahuweka; Marchella W. Sirang (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2024)
This paper contains about “Jesus as a Teacher and Counselor: Understanding the Two Main Functions in His Mission” This approach uses a qualitative method of literature approach and is descriptive analysis with the aim of describing and analyzing the two main functions in carrying out the mission of teachers and counselors. The data for this research was collected by conducting a literature study using literature studies in the form of books, articles and journals. The results of this study found that being a teacher and also a counselor must follow the example of Jesus.